Minimum costs to manufacture new treatments for COVID-19 - Andrew Hill; Junzheng Wang; Jacob Levi; Katie Heath; Joseph Fortunak (Elsevier, 2020)
Introduction: 'Repurposing' existing drugs to treat COVID-19 is vital to reducing mortality and controlling the pandemic. Several promising drugs have been identified and are in various stages of clinical trials globally. If efficacy of these drugs is demonstrated, rapid, mass availability at an affordable cost would be essential to ensuring equity and access especially amongst low- and middle-income economies. Methods: Minimum costs of production were estimated from the costs of active pharmaceutical ingredients using established methodology, which had good predictive accuracy for medicines for hepatitis C and HIV amongst others. Data were extracted from global export shipment records or analysis of the route of chemical synthesis. The estimated costs were compared with list prices from a range of countries where pricing data were available. Results: Minimum estimated costs of production were US $0.93/day for remdesivir, $1.45/day for favipiravir, $0.08/day for hydroxychloroquine, $0.02/day for chloroquine, $0.10/day for azithromycin, $0.28/day for lopinavir/ritonavir, $0.39/day for sofosbuvir/daclatasvir and $1.09/day for pirfenidone. Costs of production ranged between $0.30 and $31 per treatment course (10-28 days). Current prices of these drugs were far higher than the costs of production, particularly in the US. Conclusions: Should repurposed drugs demonstrate efficacy against COVID-19, they could be manufactured profitably at very low costs, for much less than current list prices. Estimations for the minimum production costs can strengthen price negotiations and help ensure affordable access to vital treatment for COVID-19 at low prices globally.